The 16s/23s ribosomal spacer region as a target for DNA probes to identify eubacteria. - Barry, T; Colleran, G; Glennon, M; Dunican, L K; Gannon, F

(untitled) (Genome Research, 1991)
Variable regions of the 16s ribosomal RNA have been frequently used as the target for DNA probes to identify microorganisms. In some situations, however, there is very little sequence variation observed between the 16s rRNA genes of closely related microorganisms. This study presents a general method to obtain species-specific probes using the spacer (intergenic) region between the 16s and 23s rRNA genes. The overall strategy is analogous to that which has previously been developed for the variable regions of the 16s rRNA genes. Sequence analysis of the 16s rRNA and 23s rRNA coding sequences flanking the spacer regions resulted in the design of PCR primers that can be used to amplify the spacer regions of a wide range of eubacteria. Sequencing the amplified spacer region then gives rise to the information that can be used to select specific DNA sequences for use as a DNA probe or for the generation of specific PCR primers to a microorganism of interest. In this study the approach to develop specific DNA markers for members of the genus Clostridium is described in detail. A specific DNA oligonucleotide probe and PCR primers have been designed for Clostridium perfringens that distinguish it from other organisms in the genus.